Solid Pseudopapillary Neoplasm of the Pancreas in Young Male Patients: Three Case Reports - Akira Aso; Eikichi Ihara; Kazuhiko Nakamura; Irina Sudovykh; Tetsuhide Ito; Masafumi Nakamura; Tetsuo Ikeda; Nobuyoshi Takizawa; Yoshinao Oda; Shuji Shimizu (Case Reports in Gastrointestinal Medicine)
A preoperative diagnosis of solid pseudopapillary neoplasms (SPNs) in young male patients is difficult to achieve using radiological images. We herein present three cases of young male patients with relatively small SPNs. Endoscopic ultrasound (EUS) showed well-encapsulated, smooth-surfaced, heterogeneous solid lesions in all patients, and all preoperative diagnoses were achieved by EUS-guided fine needle aspiration (EUS-FNA). The final pathological diagnosis after surgery was an SPN with a Ki-67 labeling index of <2%. SPNs should be considered even in young male patients. EUS with EUS-FNA could be a useful diagnostic modality for SPNs even in young male patients.